Hadith In Education In The Digital Era (Case Study At SMK Negeri 5 Pekanbaru) - Nurhadi; Ilyas Husti (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to discuss the hadees in education of digital age (case study at SMKN 5 Pekanbaru. This research descriptive quantitative. The conclusion of this study are 1) the use of technology-based learning media in the digital era: 60% of respondents strongly agree with the use of technology in the digital era, 25% of respondents agree, 7% of respondents are hesitant and 8% of respondents do not agree with learning using digital technology. 2) use of digital libraries : 60% of respondents stated that they did not utilize electronic book sources provided by the National Library and the Ministry of Education and Culture in the learning process, and 3) critical thinking: 43% of respondents experienced cyberbullying, 33% of respondents experienced hate speech and only 22% of students did not experience negative impacts online media.